Molecular detection of extended spectrum β-lactamases, metallo β-lactamases, and Amp-Cβ-lactamase genes expressed by multiple drug resistant Pseudomonas aeruginosa isolates collected from patients with burn/wound infections - Mahfouz Nasser; Mahmoud Ogaili; Snehal Palwe; Arun S. Kharat (Elsevier, 2020)
Objectives: his study was aimed to identify diverse β-lactamase genes produced by multiple drug-resistant Pseudomonas aeruginosa isolates procured from burn/wound infected patients hospitalized in General Al-thawrah hospital of Hodeidah city, Yemen during (July to December 2018). Methods: From 200 burn wound swabs, total 200 single strain per patient was isolated by culturing them on nutrient agar, MacConkey agar and blood agar, of which 98 were identified and confirmed as P. aeruginosa.The isolates were subjected for antibiotic susceptibility test according to the CLSI guidelines; molecular characterization of β-lactamases-encoding genes were carried out with multiplex PCR. Results: Overall, significantly high resistance was observed for ceftazidime, cefepime, gentamicin, tobramycin, amikacin and ciprofloxacin against P. aeruginosa (N = 98) with percent resistance of77.5% (n = 76), 72.4% (n = 71), 85.7% (n = 54), 74.5% (n = 73), 83.7% (n = 82), and 66.3% (n = 65), respectively. however, carbapenems showed comparatively low resistance as 20-21% while another routinely used anti-pseudomonas combination, piperacillin-tazobactam showed 54% of resistance. Out of 98 Pseudomonas studied, 65 isolates (66.3%) were found to be multi-drug resistant. Also, presence of various β-lactamases which was confirmed by PCR based amplification. Presence of various ESBLs was evident as 43% (n = 28), 30.7% (n = 20), 30.7% (n = 20), 24.6% (n = 16) and12.3% (n = 8) of isolates were identified with blaVEB, blaGES, blaCTX-M, blaOXA-10, blaTEM, and blaSHV genes respectively. Among the MBL-expressing isolates (n = 20, 30.7%) all exhibited blaVIM gene while Amp-C gene was observed in 40isolates (61.5%). Conclusion: The outcome of this study demonstrated significant increase in antibiotic resistance due to expression of diverse β-lactamases owing to increased MDR P. Aeruginosa in Yemen. We suggest antibiotic treatments comprising of combinations of antibiotics in order to preserve the utility of carbapenems and piperacillin-tazobactam in Yemen and to curb acquisition and dissemination of antibiotic resistance genes in P. Aeruginosa in this territory.